Iberian-Latin American connection : implications for U.S. foreign policy - Wiarda, Howard J., 1939- (Routledge, 2019)
This book is especially timely as Latin America is diversifying its international connections, Spain and Portugal are seeking to expand their interests and presence in Latin America, and U.S. policy toward both regions has become increasingly complex. Contributors trace the history of Iberian-Latin American relations from colonial times and then examine the cultural, economic, political, and strategic ties that currently exist between the two regions. Particular attention is focused on the impact of Iberian-Latin American relations on U.S. foreign policy. The book concludes with a section of country-specific case studies.